Multi-Walled Carbon Nanotube Reinforced Polymer as a Bonded Repair for Al 2024-T3 Fatigue Crack Growth [Crecimiento de Grieta por Fatiga en Al 2024-T3 Reparado Con Polímero Reforzado Con Nanotubos de Carbono] - Monsalve-Gonzalez, A; Artigas-Abuin, A; Solis-Vidal, R (Universidade Federal do Rio de Janeiro, 2018)
The influence on multi walled carbon nanotubes (MWCNT, or simply CNT) as a reinforcement material in an epoxy resin in order to decrease the fatigue crack propagation rate in the 2024 T3 aeronautical Al alloy was studied. CT samples were pre-cracked in a resonant fatigue machine until a 4 mm pre-crack length. Four groups of samples were considered: a non-repaired reference group, two groups repaired with epoxy resin reinforced with two CNT proportions (0.5 and 1 vol %) and a group repaired by the conventional “stop drill” technique. The crack was propagated until a length of 16 mm, measuring the number of cycles to this crack propagation. Resin Hysol EA9320 NA was used, mixing it with the CNT and the hardener, by ultrasonic stirring. S-N curves (stress vs number of cycles) were plotted obtaining an increment of 104% for a 0.5 vol% of CNT, 128% for 1 vol% of CNT and 400% for “stop drill” repairing. These results were referred to the non-repaired samples at the lower load level. These results showed that in repaired samples with CNT reinforced resin, the initiation and propagation of cracks would be delayed, constituting this method a reasonable and convenient repairing procedure useful for aeronautical cracked structures. © 2018, Universidade Federal do Rio de Janeiro. All rights reserved.